Parasitism and pathogenicity of Radopholus similis to Ipomoea aquatica, Basella rubra and Cucurbita moschata and genetic diversity of different populations - Yu LI; Ke WANG; Hui XIE; Chun-ling XU; Dong-wei WANG; Jing LI; Xin HUANG; Xiao-fang PENG (Journal of Integrative Agriculture, 2016)
Ten populations of Radopholus similis from different ornamental hosts were tested for their parasitism and pathogenicity to water spinach (Ipomoea aquatic), malabar spinach (Basella rubra), and squash (Cucurbita moschata) in pots. The results showed all three plants were new hosts of R. similis. Growth parameters of plants inoculated with nematodes were significantly lower than those of healthy control plants. All R. similis populations were pathogenic to the three plants, but pathogenicity differed among populations from different hosts. The same R. similis populations also showed different pathogenic effects in the three different plants. RadN5 population from Anthurium andraeanum had the highest pathogenicity to the three studied plants. RadN1 from A. andraeanum had the lowest pathogenicity to squash and RadN7 from Chrysalidocarpus lutesens had the lowest pathogenicity to water spinach and malabar spinach. R. similis is usually associated with root tissues, but here we report that it could be found to move and feed in the stem bases of all three studied plants. Sequence and phylogenetic analyses of DNA markers of the 18S rRNA, 28S rRNA, ITS rRNA, and mitochondrial DNA gene sequences of ten R. similis populations revealed significant genetic diversity. RadN5 and RadN6 populations from anthurium showed a close genetic relationship and could be distinguished from other populations by PCR-RFLP. At the same time, RadN5 and RadN6 populations were the most pathogenic to three studied plants. These results confirm the existence of large biological variability and molecular diversity among R. similis populations from the same or different hosts, and these characteristics are related to pathogenic variability.